Barriers in surgical research: A perspective from the developing world - Nadeem Ahmed Siddiqui; Muhammad Aanish Raees; Rehan Nasir Khan; Farhan Zafar (Journal of the Pakistan Medical Association, 2022)
Research in surgery has led to significant advances over the last century in terms of how medicine is practised in and outside the operating rooms today. Surgical research in the developed countries is responsible for most of this advancement, but it is often inapplicable in resourcelimited settings in the developing world. Lower- and middle-income countries are in a unique position to take this work further, but they are limited by certain barriers. These barriers could broadly be classified under social and cultural, infrastructure, financial, ethical, and personal categories. These barriers are often not fully realised, but can potentially be addressed with concerted efforts to continue the advancement of medicine for everyone. Continuous...